PATELLOFEMORAL JOINT - MORPHOLOGY, DYSPLASIA AND INFLUENCE ON THE ONSET OF CHONDROMALACIA OF THE PATELLA - Stamatović, Ratko; Dulović, Dragan; Vojinović, Radiša; Vasić Vilić, Jasenka; Ilić, Slađana; Nurković, Jasmin S.; Kostić, Dejan (Medicinski časopis, 2023)
The patellofemoral joint, the anterior compartment of the knee, undergoes the earliest degenerative changes throughout life and joint morphology is of great importance in the appearance of pain in the anterior knee and chondromalacia of the patella. Chondromalacia of the patella is a progressive disease with a change in normal morphology and structure, with the formation of minor or major defects in the cartilage itself and represents a significant socioeconomic problem because it occurs in young, physically active people. Quadriceps wasting, patellofemoral crepitus, and effusion are obvious clinical indications. In addition, radiological examinations are also necessary for diagnosis. Magnetic resonance imaging (MRI) is a non-invasive diagnostic method, which promises a unique ability to potentially identify cartilage lesions.
Keywords: patelofemoralni zglob; morfologija; hondromalacija